Tailoring grain growth and solid solution strengthening of single-phase CrCoNi medium-entropy alloys by solute selection. (1st October 2020) - Hu, G.W.; Zeng, L.C.; Du, H.; Liu, X.W.; Wu, Y.; Gong, P.; Fan, Z.T.; Hu, Q.; George, E.P.
Highlights: Grain growth of CrCoNi MEAs was tuned by proper choice of solute. Solutes with high SDQ lead both grain refinement and solid solution strengthening. Mo increases the yield strength by ∼40 % while retaining excellent ductility (49 %). Mo shows a significant solute-drag effect while Al has the opposite effect. Abstract: In the present study, we selected solutes to be added to the CrCoNi medium-entropy alloy (MEA) based on the mismatch of self-diffusion activation energy (SDQ) between the alloying elements and constituent elements of the matrix, and then investigated their grain growth behavior and mechanical properties. Mo and Al were selected as the solutes for investigation primarily because they have higher and lower SDQ, respectively, than those of the matrix elements; a secondary factor was their higher and lower shear modulus. Their concentrations were fixed at 3 at.% each because previous work had shown these compositions to be single-phase solid solutions with the face-centered cubic structure. Three alloys were produced by arc melting, casting, homogenizing, cold rolling and annealing at various temperatures and times to produce samples with different grain sizes. They were (a) the base alloy CrCoNi, (b) the base alloy plus 3 at.% Mo, and (c) the base alloy plus 3 at.% Al. The activation energies for grain growth of the CrCoNi, CrCoNi-3Mo and CrCoNi-3Al MEAs were found to be ∼251, ∼368 and ∼219 kJ/mol, respectively, consistent with the notion that elements with higher SDQ (in this study Mo) retard grain growth (likely by a solute-drag effect), whereas those with lower values (Al) accelerate grain growth. The room-temperature tensile properties show that Mo increases the yield strength by ∼40 % but Al addition has a smaller strengthening effect consistent with their relative shear moduli. The yield strength as a function of grain size for the three single-phase MEAs follows the classical Hall-Petch relationship with much higher slopes (＞600 MPa μm −0.5 ) than traditional solid solutions. This work shows that the grain growth kinetics and solid solution strengthening of the CrCoNi MEA can be tuned by selecting solute elements that have appropriate diffusion and physical properties.